Los pictogramas para fomentar la lectura en niños de 3 a 4 años de edad de la unidad educativa "Ángel Polibio Chaves" cantón Guaranda, provincia Bolívar, periodo 2024 - Aguachela Caspi, Marcia Raquel (2025)
The purpose of this research project is to investigate and evaluate the use of pictograms as elements that encourage reading in children aged 3 to 4 years, which make up the initial level I. The study has a qualitative approach, an exhaustive analysis was proposed regarding the implementation of this type of material that can impact in a positive way to guide children towards reading in a fun and creative way. Pictogram books as teaching material are a crucial part to activate curiosity, interest and learning in a participatory, fun and meaningful way. This study provides a valuable contribution to the field of early education since it is one of the tools that facilitates teaching and understanding children's texts in an easy way. The constant use of pictograms is essential, thereby introducing them to the world of reading and creating a habit that will be useful for the rest of their lives. Reading in early childhood is important for the development of creativity and imagination in every child. However, many young children struggle with written words, which can delay their learning. Pictograms, as graphic representations that illustrate concepts, are a powerful tool for overcoming this barrier, as young learners can easily connect images with words and their meaning.